COIL as a Way to Enhance Internationalization: Balancing Evidence and Proliferation - Gelashvili, Maia; Blanco, Gerardo (International Higher Education, 2024)
Collaborative Online International Learning (COIL) is a form of virtual exchange that institutions can use to internationalize the curriculum and foster internationalization at home. COIL promises more equitable and inclusive ways to achieve internationalization and global learning for all students. Even though COIL has existed for the last 20 years, it became truly widespread only during the COVID-19 pandemic. To explore its full potential, accurate implementation and more evidence is needed.